Shopping for water : how the market can mitigate water shortages in the American West - Culp, Peter W.; Glennon, Robert Jerome, 1944-; Libecap, Gary D. (Discussion paper (Hamilton Project), 2014)
The American West has a long tradition of conflict over water. But after fifteen years of drought across the region, it is no longer simply conflict: it is crisis. In the face of unprecedented declines in reservoir storage and groundwater reserves throughout the West, we focus in this discussion paper on a set of policies that could contribute to a lasting solution: using market forces to facilitate the movement of water resources and to mitigate the risk of water shortages.